2022
DOI: 10.1590/0103-8478cr20210022
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of resource use efficiency in corn production: a two-stage data envelopment analysis approach in Turkey

Abstract: This research analyzed the efficiency situation of corn farms operating in the Adana province of Turkey. In this context, required farm management data were collected from 111 corn farmers by using face to face survey method during the 2019-2020 cultivation season. To determine the technical efficiency (TE) levels of corn farms, Data Envelopment Analysis (DEA) was applied. Furthermore, factors that cause the inefficiency in corn farms were detected by using the Tobit regression model. According to research res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 22 publications
(21 reference statements)
0
2
0
2
Order By: Relevance
“…With the Mosaic occupation of cultivated land by other land types, especially the continuous expansion of rural settlements and urban construction land, and the rapid development of the transportation network, the fragmentation of cultivated land continues to increase, hindering the promotion of mechanical equipment and large-scale agricultural technology, which is not conducive to the intensive production of grain and is bound to affect grain production. Berk (2022) also concluded that agricultural land fragmentation may lead to inefficiency [7]. The distance of cultivated land has a positive correlation with grain output, indicating that in recent years, with the shift of the center of gravity of cultivated land to the urban periphery, the distance between it and the administrative center has increased, and the probability of land being used for urbanization construction has become smaller and smaller.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the Mosaic occupation of cultivated land by other land types, especially the continuous expansion of rural settlements and urban construction land, and the rapid development of the transportation network, the fragmentation of cultivated land continues to increase, hindering the promotion of mechanical equipment and large-scale agricultural technology, which is not conducive to the intensive production of grain and is bound to affect grain production. Berk (2022) also concluded that agricultural land fragmentation may lead to inefficiency [7]. The distance of cultivated land has a positive correlation with grain output, indicating that in recent years, with the shift of the center of gravity of cultivated land to the urban periphery, the distance between it and the administrative center has increased, and the probability of land being used for urbanization construction has become smaller and smaller.…”
Section: Discussionmentioning
confidence: 99%
“…Yadava et al (2021) used the DEA method to calculate the technical efficiency of fertilizer use in India [5]. Salam et al (2022) used the DEA method to calculate the technical efficiency of grain production in Punjab [6], and Berk et al (2022) used the DEA method to calculate the resource utilization efficiency in corn production in Turkey [7]. The DEA method can only assess relative efficiency and ignores the effect of random errors.…”
Section: Introductionmentioning
confidence: 99%
“…Assim, o gestor da propriedade rural precisa considerar de forma estratégica, por exemplo, a definição da semente e dos insumos na lavoura e sua produtividade, sem ignorar os aspectos econômicos, financeiros, ambientais, sociais e culturais que qualificam a decisão (Deponti et al, 2018;Diamor & Sudré, 2021) e aumentam o bem-estar da família (Schneider & Freitas, 2013). As funções básicas do administrador rural são: administrar com eficiência os bens de produção; conservar, investir e cuidar do patrimônio; aumentar a produtividade e gerenciar os custos de produção; adotar tecnologias de informação, comunicação e automação; produzir e garantir renda com eficiência técnica (Silva, 2009;Berk, Güney & Sangün, 2022).…”
Section: Administração E Produtor Ruralunclassified
“…Essas questões foram discutidas por Villwock, Germani e Roncato (2016) na perspectiva socialmente construída no que se refere às diferenças de gênero e a masculinização do espaço rural enraizada na história da sociedade brasileira(Andrade et al, 2009). Novas possibilidades de inserção das mulheres nas atividades agrícolas de forma homogênea são possíveis (Graziano daSilva, 1997;Villwock, Germani & Roncato, 2016).Nesse sentido, apoiando-se em diferentes autores(Deponti et al, 2018;Bianchi et al, 2019;Berk, Güney & Sangün, 2022), afirmamos que a eficiência técnica na produção de grãos depende da experiência no processo de plantio e colheita, do número de tratores/colheitadeiras e extensão de terra, mas a escolaridade dos participantes da decisão, a apropriação das tecnologias de gestão e as planilhas de custos qualificam a decisão. Na gestão da propriedade, a família Santos conta com o apoio da Cooperativa Agrícola Alfa, da qual são sócios fundadores.…”
unclassified